Digital Discourse on Bottled Drinking Water: A Social Network Analysis and NLP Approach - Maryam kassem Maryam kassem; Vanessa Ghafar Vanessa Ghafar; Asep Miftahuddin Asep Miftahuddin (Apollo: Journal of Tourism and Business, 2026)
This study aims to examine digital public discourse regarding bottled drinking water on X/Twitter using a multidimensional social media analytics approach. The data consisted of 714 public conversations collected through the SocialX platform during the observation period from January to May 2026. Several computational analytical techniques were employed, including sentiment analysis, emotion analysis, text network analysis (TNA), social network analysis (SNA), trend analysis, and zero-shot classification. The findings reveal that public conversations were predominantly characterized by neutral and positive orientations, indicating that bottled drinking water is generally perceived as a practical and widely accepted consumption product. Emotion analysis further demonstrates that “happy” was the dominant emotional category, reflecting routine and functional consumption experiences within digital discussions. Text network analysis identified several interconnected thematic clusters related to bottled drinking water consumption, pricing, packaging, environmental concerns, and microplastic issues. In addition, the social network structure showed moderately fragmented interaction patterns centered around several influential accounts rather than a fully centralized communication network. Trend analysis also indicated a continuous increase in discussion intensity throughout the observation period, suggesting growing public attention toward bottled drinking water and sustainability-related issues. Overall, this study provides a comprehensive understanding of digital discourse surrounding bottled drinking water and contributes to the literature on consumer communication, social media analytics, and sustainability discourse in online environments.